Kajian metode Subjective Global Assessment (SGA) dan Nutrition Services Screening Assesment (NSSA) sebagai status gizi awal pasien dewasa sebagai prediktor lama rawat inap dan status pulang - Agustinus I Wayan Harimawan; Hamam Hadi; Susetyowati Susetyowati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2011)
Background: Assessment of nutrition status of newly hospitalized patients is an initial stage of nutrition intervention which will bring effects to the duration of stay and the history of patients' diseases during hospitalization. Appropriate nutrition intervention as part of patients' care can be used as an indicator of the quality of hospital service.Objective: The study aimed to identify preliminary nutrition status of newly hospitalized adult patients using SGA method, its effects to length of stay and status of discharge and compare the capacity of SGA and NSSA indicators in predicting length of stay and status of discharge of adult patients.Method: This observational study used prospective cohort study design. It was carried out at Anuntaloko Hospital of Parigi, District of Parigi Moutong, Sulawesi Tengah from July to September 2008. Subject consisted of 162 people comprising 82 undernourished people and 80 people with good nutrition status based on assessment using SGA method. Data analysis used bivariable and multivariable, receiver operating characteristics (ROC) curve and diagnostic methods using computer program.Result: The majority of newly hospitalized patients were undernourished (50.6%); preliminary status of patients assessed using SGA method could affect length of stay, relative risk (RR)=3.67 but not status of discharge (RR=0.97). The capacity of SGA indicator, area under the curve (AUC)=0.81 and maximum sum of sensitivity and specifcity (MSS) =1.57 was better than NSSA indicator (AUC=0.76 and MSS 1.43) in predicting length of stay. The capacity of SGA indicator (AUC=0.50 and MSS=1.01) was better than NSSA indicator (AUC=0.49 and MSS=0.98) in predicting discharge status of the patient.Conclusion: SGA and NSSA indicators could be implemented in assessing preliminary nutrition status of newly hospitalized adult patients; SGA indicator had better capacity than NSSA indicator.